Pengaruh Penambahan Partikel Penguat Zirkonia (ZrO2) terhadap Karakteristik Komposit Bermatriks Al-13.20Zn- 6.38Mg-6.67Si-1.38Cu setelah Pengerasan Penuaan untuk Aplikasi Balistik - Nuzulian Akbar Arandana; Socania Titi Nayoka; Bondan Tiara Sofyan (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2018)
One of the main requirement for a tactical vehicle is the ability to withstand the penetration of bullet so as to ensure the safety of troops inside. Steel is commonly used for the body of a tactical vehicle due to its high strength and toughness. However, steel is heavy so that reduces the mobility of the vehicle. Therefore, new materials, which are light and tough, are developed to substitute steel. One alternative is aluminium composites, which are strengthened with ZrO2 particulates that have high fracture toughness. The composites may be heat treated to further improve their mechanical properties.In this research, Al-13.20Zn-6.38Mg-6.67Si-1.38Cu (wt.%) composites with addition of 5, 7.5, and 10 vol. % ZrO2 particulates were fabricated by squeeze casting. To improve their toughness, the composites were solution treated at 450 oC for 1 hour, and then aged at 200 oC. Material characterizations consisted of Rockwell B hardness testing to construct age hardening curves, impact testing, microstructure observation by using optical microscope and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). The ballistic testing was conducted on a stack of three plates of composites with 7.5 vol. % ZrO2, in accordance to NIJ 0108.01 standard with 7.62 mm bullet from the distance of 15 m. The results showed that the peak hardness was achieved after 2 hours of ageing. The highest peak hardness was achieved by samples with 7.5 vol. % ZrO2, with the value of 71.48 HRB. The impact values showed opposite trend when compared to hardness values. The microstructures in the overaged condition consisted of Mg2Si and MgZn2 second phases, together with ZrO2 particulates which were clustered and initiated porosity. Three layers of composite were not able to withstand 7.62 mm bullet penetration, however, the composites showed considerable plastic deformation indicating potential to absorb high velocity impact energy from the bullet.